The supernatural sublime : the wondrous ineffability of the everyday in films from Mexico and Spain - Rodríguez-Hernández, Raúl; Schaefer, Claudia, 1949- (New hispanisms., 2019)
"The Supernatural Sublime explores the long-neglected element of the supernatural in films from Spain and Mexico"--